Novel organic selenium source hydroxy-selenomethionine counteracts the blood-milk barrier disruption and inflammatory response of mice under heat stress - Zheng, Yuhui; Zhao, Yanyan; He, Wenjun; Wang, Yajing; Cao, Zhijun; Yang, Hongjian; Wang, Wei; Li, Shengli (Frontiers in Immunology, 2022)
Heat stress (HS) in summer has caused huge economic losses to animal husbandry production recently. When mammary gland is exposed to high temperatures, it will cause blood-milk barrier damage. Hydroxy-selenomethionine (HMSeBA) is a new selenium source with better guarantee of animals’ production performance under stress, but whether it has protective effect on heat stress-induced blood-milk damage is still unclear. We established mammary epithelial cells and mice heat stress injury models to fill this research gap, and hope to provide theoretical basis for using HMSeBA to alleviate heat stress damage mammary gland. The results showed that (1) Heat stress significantly decreases in vitro transepithelial electrical resistance (TEER) and cell viability (P < 0.01), and significantly decreases clinical score, histological score, and total alveoli area of mice mammary gland tissue (P < 0.01). (2) HMSeBA significantly increases TEER and fluorescein sodium leakage of HS-induced monolayer BMECs (P < 0.01), significantly improves the milk production and total area of alveoli (P < 0.01), and reduces clinical score, histological score, mRNA expression of heat stress-related proteins, and inflammatory cytokines release of heat-stressed mice (P < 0.01). (3) HMSeBA significantly improves tight junction structure damage, and significantly up-regulated the expression of tight junction proteins (ZO-1, claudin 1, and occludin) as well as signal molecules PI3K, AKT, and mTOR (P < 0.01) in heat-stressed mammary tissue. (4) HMSeBA significantly increases glutathione peroxidase (GSH-Px), total antioxidant capacity (T-AOC), and superoxide dismutase release (SOD) (P < 0.01) and significantly reduce malondialdehyde (MDA) expression (P < 0.01) in heat-stressed mammary tissue. In conclusion, this study implemented heat-stressed cell and mice model and showed that HMSeBA significantly regulate antioxidant capacity, inhibited inflammation, and regulate tight junction proteins expression in blood-milk barrier via PI3K/AKT/mTOR signaling pathway, so as to alleviate mammary gland damage and ensure its structure and function integrity.